VALUE OF MRI IN MULTIMODAL TREATMENT OF LOCALLY ADVANCED RECTAL CARCINOMA - Ana Lazarova; Andrej Nikolovski; Vasilevska Nikodinovska, Violeta (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2020)
MRI is a basic tool in patient selection for preoperative neoadjuvant treatment of rectal carcinoma, with assessment of stage reduction. The aim of the paper was to evaluate chemoradiotherapy effects in advanced stage rectal carcinoma by comparison of MRI findings before and after chemoradiotherapy. Material and methods: Prospectively, MRI findings of 15 patients with rectal carcinoma confirmed at colonoscopy, were evaluated. In all patients preoperative neoadjuvant treatment was done and MRI restaging was performed after 6 to 8 weeks. MRI standard protocol was done on 1.5T machine, sagital T2WI, axial T1WI, T2WI and DWI. On MRI was assessed tumor and nodal stage, presence of extramural vascular invasion (EMVI), tumor localization within the rectum (low, medium, high rectum, recto-sigmoid junction). Computer tomography was performed in all patients for distant metastases assessment. Results: Out of 15 patients, 12 (66.7%) were male, and 3 (33.3 %) were female, with a mean age of 65 years (range 50 to 80years). Six cases had middle rectum localization, 6 cases in low rectum, and 3 patients had recto-sigmoid localization. At initial MRI, 7 cases (46.6%) had MR signs for T3 stage, and 8 cases (53.3%) had T4 stage. Comparison of MRI results before and after chemoradiotherapy showed stage decreasing in 5(33.3%), from T4 to T3 stage. In 11 patients (73.7%), EMVI after therapy became negative with a statistically significant difference before and after chemoradiotherapy. All patients before therapy had different numbers of metastatic lymph nodes in mesorectum, with number reduction in all cases after therapy and two patients were without metastatic lymph nodes. Conclusion: MRI has a significant value in pre- and post-neoadjuvant therapy assessment of resection margins involved by tumor, positive extramural vascular invasion, and metastatic lymph node around resection margins. This is important for operative planning in order to avoid extensive resection with surgery techniques that preserve the anal sphincter.